Profitability, Leverage, Activity, And Liquidity as Determinants of Financial Distress in Property and Real Estate Companies Listed on the IDX - Vallesca Irene Thejatirta; Sufiyati Sufiyati (Universitas KH. Abdul Chalim Mojokerto, 2026)
The continuity of a company’s operations depends on maintaining a stable financial condition. One of the critical risks that may disrupt business sustainability is financial distress, a situation in which a company experiences severe financial pressure that may lead to bankruptcy. The potential occurrence of financial distress can be identified through financial statements, where financial ratios are used to evaluate the company’s ability to generate profits, meet obligations, and manage its assets and liabilities. This study aims to examine the effect of profitability, leverage, activity, and liquidity on financial distress in property and real estate companies listed on the Indonesian Stock Exchange (IDX) during the 2021-2024 period. Financial distress is measured using the Altman Z-Score model. The sample was selected using a purposive sampling method based on predetermined criteria, resulting in 170 financial statement observations. Data processing and analysis were performed using multiple linear regression through SPSS software. The results show that profitability and liquidity have significant effects in reducing financial distress, while leverage has a significant positive effect on financial distress. Meanwhile, activity does not have a significant effect on financial distress. These findings highlight that managing profitability and liquidity is crucial for minimizing financial distress risk, whereas excessive debt levels may worsen a company’s financial condition.